Determinan Perilaku Seksual Berisiko pada Remaja Makassar (Studi Kasus Santri Darul Arqam Gombara dan SMAN 6) - masni, Masni; Hamid, St. Fatima (Media Kesehatan Masyarakat Indonesia, 2018)
Adolescence is a period great curiosity and want to try to imitate what they seen or heard. Curiosity makes teens more permissive to engage in risky sexual behavior, but it is suspected that religious understanding will be a distinguishing factor. This study aims to determine the influence of religious understanding, parent role, peer role and the use of social media against risky sexual behavior in adolescents by comparing the santri Madrasah Aliyah in Darul Arqam Gombara Pesantren with students of SMAN 6 Makassar. Observational research with cross sectional study design, involving 79 students of MA Darul Arqam Gombara selected as sample and 274 students of SMAN 6 selected proportional stratified random sampling. The analysis used univariate and bivariate analysis with chi-square test and phi test. The result of the research shows that there is influence of parent role in MA Darul Arqam (p=0,000, φ=0,403) to santri risk sexual behavior whereas student in SMAN 6 there is no influence of parent role (p=0,472) towards sexual risk behavior. The influence of religious understanding (p=0.027, φ=0.134), peers (p=0,000, φ=0.339) and social media (p=0.035, φ=0.128) in SMAN 6 on risky sexual behavior in students whereas in MA Darul Arqam showed no influence of religious understanding (0,811), peer role (0,702) and social media (0,063) toward risky sexual behavior at santri.